Mediation: native disputes - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (The Malaysian Current Law Journal Sdn Bhd, 2020)
This chapter discusses the application of mediation in resolving customary disputes with reference to its practice in the native courts of the states of Sabah and Sarawak.